Hemorrhoidectomy with lateral ultrasonic dissection in geriatric patients - N. A. Maistrenko; A. A. Sazonov; P. N. Romashchenko; A. G. Ardankin (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to evaluate the efficacy and safety of hemorrhoidectomy with lateral ultrasound dissection in patients of older age groups.  METHODS AND MATERIALS. A comparative analysis of the immediate and long-term results of treatment in two groups of geriatric patients suffering from III–IV stages of hemorrhoids was carried out. The main included 27 patients who underwent hemorrhoidectomy using the original technique of lateral ultrasound dissection in the «cutting» mode. The control group consisted of 33 patients who underwent traditional Milligan–Morgan hemorrhoidectomy using electrocoagulation. To assess the traumaticity degree of interventions using light microscopy, pathomorphological changes in remote hemorrhoids were studied, and the dynamics of the wound process was traced.  RESULTS. The incidence of postoperative complications in the main and control groups was 7 % and 27 % (p=0.09). When assessing the dynamics of the intensity of the pain syndrome within 5 days after the intervention, significantly lower indicators were found in patients who underwent hemorrhoidectomy with lateral ultrasound dissection, which made it possible to significantly reduce the doses of analgesics. A comparative analysis of pathomorphological changes showed statistically differences in the extent of the coagulation necrosis zone, which was significantly less in patients of the main group.  CONCLUSION. The use of hemorrhoidectomy with lateral ultrasound dissection in geriatric patients reduces the incidence of complications and the intensity of the pain syndrome, as well as speed up their rehabilitation.